The severity assessment of critically ill preeclamptic women: a case-control study A avaliação de gravidade de mulheres em estado grave por pré-eclâmpsia: estudo caso-controle - João Paulo Souza (Revista Brasileira de Terapia Intensiva, 2006)
BACKGROUND AND OBJECTIVES: The assessment of illness severity and prognosis of obstetric patients by scoring systems is still a controversial issue. Preeclampsia is a leading cause of severe maternal morbidity and mortality, and a major cause of obstetric admission to intensive care unit. There is paucity of data regarding the predictability of critically ill preeclamptic women and the application of scoring systems to this population. This study aimed to evaluate and compare the application of APACHE II, SAPS II and MPM II scoring systems between a preeclamptic population and a non obstetric female population. METHODS: A case-control study was conducted on 28 preeclamptic women and 56 non obstetric female patients, admitted to a general intensive care unit over a period of 10 years. The predictive accuracy of the prognostic evaluation systems was estimated by the area under the receiver operator characteristic curve. RESULTS: The mortality rate was 21.4% (6:28) for the study group and 35.7% (20:56) for the control group, with an OR = 0.49 (95%CI = 0.17-1.41). The main causes of ICU admission of preeclamptic women were HELLP syndrome, coma and pulmonary edema. In the preeclamptic population, only the MPM II score showed an area under the ROC curve statistically different from 0.500, while in the control group, all scoring systems had their areas under the ROC curves statistically different from 0.500. CONCLUSIONS: The application of APACHE II and SAPS II to evaluate critically ill preeclamptic women may be not appropriate. JUSTIFICATIVA E OBJETIVOS: A avaliação de gravidade e do prognóstico de pacientes obstétricas através de escores é ainda tema controverso, sendo escassa a informação sobre mulheres com pré-eclâmpsia. Esta é uma das maiores causas de morbidade materna grave e de mortalidade materna, além de ser também uma das principais causas de internação obstétrica em UTI. Os objetivos deste estudo foram avaliar e comparar a aplicação do APACHE II, SAPS II e MPM II em população de mulheres com pré-eclâmpsia e em população feminina não-obstétrica. MÉTODO: Foi realizado um estudo caso-controle com 28 mulheres pré-eclâmpticas e 56 pacientes femininas não-obstétricas admitidas em unidade de terapia intensiva geral, num período de 10 anos. A acurácia preditiva dos sistemas de avaliação prognóstica foi estimado através da área sob a curva ROC. RESULTADOS: A taxa de mortalidade no grupo de estudo foi de 21,4% (6:28) e 35,7% (20:56) no grupo controle, com OR = 0,49 (95%CI = 0,17-1,41). As principais causas de admissão à UTI de mulheres com pré-eclâmpsia foram: síndrome HELLP, coma e edema pulmonar agudo. Na população com pré-eclâmpsia, apenas o escore MPM II mostrou uma área sob a curva ROC estatisticamente diferente de 0,500, enquanto que no grupo controle, todos os sistemas de escore apresentaram uma área estatisticamente diferente de 0,500. CONCLUSÕES: De acordo com os achados do presente estudo, concluímos que a aplicação do sistema APACHE II e SAPS II para avaliar mulheres com pré-eclâmpsia em estado grave de saúde é possivelmente inapropriado.